Pattern of use of hydroxychloroquine as prophylaxis among health care workers against COVID-19: a KAP study - Singh, Madhusudan; Saurabh, Sushant; Ali, Obaid; Tripathi, Saparya; Pathak, Vineet Kumar; Krishna, Ekta (International Journal Of Community Medicine And Public Health, 2021)
Background: Hydroxychloroquine (HCQs) was one of the first chemoprophylaxis that received the recommendation for coronavirus disease 2019 (COVID-19). ICMR also time to time revised the guidelines for the use of HCQs as a prophylactic agent against COVID-19. But its mechanism of action for the same and duration of use was not much supported by available evidence. Hence, we conducted a web-based survey among Health Care Workers (HCWs) to know their Knowledge attitude practice (KAP) on HCQs use. Methods: We used a web-based questionnaire through google form which was circulated through snowball technique among health care worker working in a various hospital set up through various social media over a period of 1-month. Results: In our study total 159 HCWs responded to questionnaire. 37.1% (59/159) HCWs had taken HCQs, out of which 13.2% (21/59) participants acquired SARS-CoV-2 infection. Out of suffered HCWs, 38% (8/21) had taken full 7 weeks regime. Also, 84.7% (50/59) participants responded that they were confused whether to continue further taking HCQ after completing 7 weeks HCQ regimen or before every turn of their COVID duty. Conclusions: ICMR recommended its use in early phase of COVID-19 when there was not sufficient data available about its treatment and prophylaxis. But with the coming evidences we now know that there is limited role of HCQ in terms of prophylactic agent against SARS-CoV-2.